Beloved : a novel - Morrison, Toni (Picador, 1987)
"Staring unflinchingly into the abyss of slavery, this novel transforms history into a story as powerful as Exodus and as intimate as a lullaby. Sethe, its protagonist, was born a slave and escaped to Ohio, but eighteen years later she is still not free. She has too many memories of Sweet Home, the beautiful farm where so many hideous things happened. And Sethe's new home is haunted by the ghost of her baby, who died nameless and whose tombstone is engraved with a single word: Beloved."--BOOK JACKET.